Association between dietary patterns and different obesity phenotypes among Inner Mongolia adults: a cross-sectional study - Liu, Xin; Wang, Pengpu; Wang, Xinyan; Han, Ke; Zheng, Huiqiu; Zhao, Jing; Du, Qianqian; Zhou, Bowen; Wu, Bowen; Wang, Xuemei (Frontiers in Nutrition, 2025)
BackgroundThis study aimed to investigate the association between dietary patterns and obesity phenotypes among adults in Inner Mongolia using the Chinese Dietary Balance Index (DBI-22).MethodsA cross-sectional study was conducted among adults in Ordos, Inner Mongolia. Sociodemographic information, lifestyle, and physical activity were collected using a comprehensive questionnaire. Dietary data were collected with a validated semi-quantitative food frequency questionnaire (FFQ) to assess participants’ dietary intake over the past year. Body mass index (BMI) and metabolic status were measured through physical examinations and biochemical tests. Principal component analysis (PCA) was used to identify dietary patterns. A generalized linear model was applied to assess the association between the DBI-22 and dietary patterns. Multinomial logistic regression was performed to investigate the association between dietary patterns and obesity phenotypes.ResultsThree dietary patterns were identified in Mongolia: the plant-based dietary pattern, the northern pastoral dietary pattern, and the northern traditional dietary pattern. Using metabolically healthy non-obesity (MHNO) as the reference group, higher adherence to the northern pastoral dietary pattern increased the risk of metabolically healthy obesity (MHO, OR 1.44, 95% CI 1.0, 2.08) but decreased the risk of metabolically unhealthy non-obesity (MUNO, OR 0.70, 95% CI 0.54, 0.91). Higher adherence to the plant-based dietary pattern was associated with a reduced risk of MHO (OR 0.65, 95% CI 0.47, 0.91). Higher adherence to the northern traditional dietary pattern was linked to an elevated risk of metabolically unhealthy obesity (MUO, OR 1.57, 95% CI 1.2, 2.06). Generalized linear models showed that the plant-based dietary pattern and the northern pastoral dietary pattern demonstrated relatively balanced nutritional characteristics, while the northern traditional dietary pattern was characterized by relative imbalance.ConclusionAdherence to the northern pastoral dietary pattern increased the risk of MHO and reduced the risk of MUNO, while adherence to the plant-based dietary pattern reduced the risk of MHO. Both patterns demonstrated balanced diet quality. In contrast, adherence to the nutritionally imbalanced northern traditional dietary pattern increased the risk of MUO, highlighting the need for nutritional intervention.